2008
DOI: 10.1136/sti.2008.032482
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-provided screening and brief intervention for risky alcohol consumption by sexual health clinic patients

Abstract: Objectives: Brief intervention for excessive alcohol consumption is effective yet not implemented widely. Alcohol misuse is implicated in unsafe sex and sexually transmitted infections and is common in clients of sexual health services. Our aims were to assess feasibility, acceptability and effectiveness of screening and brief intervention for risky alcohol consumption by a nurse in a sexual health clinic. Methods: Patients completed the AUDIT questionnaire on handheld computers. Those scoring >8 on AUDIT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 14 publications
3
35
0
Order By: Relevance
“…The follow-up survey included the modified AUDIT used at baseline, but as has been conducted previously, the time frame was modified to avoid overlap of the pre-and posttest periods (Lane et al, 2008). Specifically, questions referred to the 6 weeks prior to the survey, rather than usual 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…The follow-up survey included the modified AUDIT used at baseline, but as has been conducted previously, the time frame was modified to avoid overlap of the pre-and posttest periods (Lane et al, 2008). Specifically, questions referred to the 6 weeks prior to the survey, rather than usual 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Lane and colleagues compared the effects of brief intervention for risky drinking delivered by a trained nurse in a sexual health clinic in Sydney, Australia, among 184 people. 21 They found a small, non-statistically significant difference in the proportion of people drinking harmfully among those who did and did not receive a brief intervention. Three months after randomisation, 46% of those in the active arm of the trial and 39% in the control arm were drinking excessively according to AUDIT-C (a three-item quantity frequency measure of alcohol consumption derived from the 10-item Alcohol Use identification test).…”
Section: Comparison With Results Of Other Studiesmentioning
confidence: 99%
“…16,21 This remains an important level of attrition, and the intervention effect observed in the completers could be a biased estimate of the effect in all participants, especially if the intervention had a different effect in the non-responders, or if the intervention affected the chance of response. However, the response rate was not highly different between the arms, and we perform different sensitivity analyses to see how missing data could have affected the results.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for being optimistic about the prospects for ABI in this setting are that surveys have repeatedly demonstrated that a high proportion of those attending sexual health clinics are drinking above recommended levels and that people who drink excessively are more likely to be diagnosed with a sexually transmitted infection. There was also evidence from previous research that ABI in sexual health clinics did reduce alcohol consumption (Lane, Proude, Conigrave, de Boer, & Haber, 2008). Yet the results of this large, rigorously conducted, pragmatic, randomised controlled trial failed to show clinically significant reductions in alcohol consumption among excessive drinkers or provide evidence of a cost-effective use of resources.…”
mentioning
confidence: 97%